A atuação do terapeuta ocupacional em unidade de terapia intensiva: uma revisão sistemática - BITTENCOURT, Estéfanny da SIlva (2023)
Introduction: The participation of the occupational therapist (OT) in Intensive Care Units (ICU) is still discreet in Brazil, perhaps because of this, there is a little discussion of interventions and insertion of this professional in this area. Objective: To synthesize the actions of OT to restore function in adult patients admitted to the ICU most frequently described in the specialized literature. Method: Systematic review based on the PRISMA recommendation. The search for the studies was carried out on the Cochrane, PubMed, OTSeek, and PEDro platforms using the search terms “Occupational Therapy”, in the title or abstract, (AND) “Intensive Care Unit” (OR) “Critical Illness” (OR) “Critical Care”, in other parts of the text. English-language texts published in the last 20 years were included and texts that describe interventions in pediatric/neonatal ICU, psychiatric diseases, and review articles were excluded. Two independent researchers selected the articles and the agreement was submitted to Kappa analysis. The level of evidence and methodological quality of the included studies were assessed using the PEDro Scale and the Cochrane Collaboration Tool, respectively. Results: The main interventions were related to the training of Activities of Daily Living (ADLs) and tasks related to Instrumental Activities of Daily Living (IADLs). These private attributions of the profession occurred isolated or with physiotherapists. The sessions, excluding the contraindication criteria, took place early (24-48h). Conclusion: The findings show early mobilization interventions, followed by ADLs/IADLs training and it is also noted that the work of the occupational therapist in the ICU is under development. Studies on other effects of prolonged ICU stay should be conducted. PROSPERO record: CRD42020214615.